The Mastery level of Sixth-grade Female Students in the Kingdom of Saudi Arabia of the Skills of Mathematical Writing and Mathematical Speaking through Electronic Media - Al-Ghamdi, Sarah Abdullah; Al-Khabti, Najla Ali (Journal of Curriculum and Teaching Methodology, 2023)
The aim of the current research is to identify the level of mastery of sixth grade students in the Kingdom of Saudi Arabia of the skills of mathematical writing and mathematical speaking through electronic media, and to achieve the goal of the research the descriptive survey methodology was used, and the research tool was an electronic test which depended on writing and speaking through electronic media, and the research tool was applied to a sample consisting of (650) students of the sixth grade primary level in Jeddah. The results revealed that the level of mastery of sixth grade primary students of mathematical writing through electronic media is low, with an average calculation of (4.88) out of (10) and a percentage of (48.8%), and in the same context the results showed that the level of mastery of sixth grade students of the primary grade of mathematical speaking through electronic media skill is low, with an average calculation of (3.61) out of (10) and a percentage (36.1%), and in light of the results of the research, the researchers made a number of recommendations, the most important of which are: the need to train teachers on the methods of developing the skills of writing and speaking through electronic media for primary school students.